Komitmen Organisasi Terhadap Kinerja ZIS Consultant Amil Zakat Yatim Mandiri - Edith Iryanto Deka Api; Dhuihita Mahardhika Lakshita; Nafia Ilham Qurrotu’aini (Universitas Islam Negeri Alauddin Makassar, 2020)
The best performance can be achieved if members are committed to the organization. The purpose of this study was to determine the organizational commitment, performance, and influence of the three components of organizational commitment, namely affective commitment, ongoing commitment and normative commitment to the performance of ZIS Amil Zakat Foundation Yatim Mandiri Consultants. There are 78 ZIS Consultants in the population. The research sample was taken using the simple random sampling method so that a sample of 65 was obtained. The data were obtained by distributing questionnaires and analyzed with the application of SPSS 20.0. The results of the study revealed that the commitment and organizational performance of the ZIS Foundation Consultant Amil Zakat Yatim Mandiri was in the high category. Organizational commitment significantly and positively influences the performance of ZIS Consultants with a 60% contribution effect. The most dominant affective commitment influence on the performance of ZIS Consultants with the influence of 19.98% contribution.